(3GdMb GdeHjfs - (3GdMdj, GdLfGLj, GdfLaj, ef Bd cGTa GdZWGA, LYaQ Hf NVQ Hf TdGd, J (B1227 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj Ndb GdEfSGf(B...(3hHYO aEfg bGeJ GdMQH Ydi SGbs
(3BNQgG (B:s
(3hcPG GdMGd aj ChGeQ GdMcGe hGdehGdj hfMhge(B...(3ceG dG jNai JeJ GdQSGdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B2(3,U(B124s
(3eYLe GdeDdajf(B:(3L(B1(3,U(B491s
(3GdPQjYI(B:(3L(B7(3,U(B45(3,Qbe(B190s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3CUhd Gdabgs